2020
DOI: 10.3390/biom10020232
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Characterization of Sea Bass Processing By-Products

Abstract: The consumption of functional foods and nutraceuticals is gaining more importance in modern society. The exploration of alternative sources and the utilization of by-products coming from the food industry are gaining more importance. The present study aimed to characterize the nutritional value and potential use of sea bass by-products as a source of high-added-value compounds for the development of supplements. The chemical composition (moisture, protein, fat, and ash contents) and profiles of amino acids (hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 45 publications
(63 reference statements)
7
33
0
Order By: Relevance
“…Moreover, the essential amino acid index (EAAI) calculated for the abdomen and chelae meat of F. limosus was 151.53% and 145.94%, respectively, and it was higher than that for the reference standard protein ( Table 4 ). The EAAI values in this study are higher comparing with the meat of several species, e.g., 114% in lagoon crab Calinectes latimanus [ 77 ], 89% in innards N. maculatus [ 78 ], 50.4–82.9% in chicken [ 75 , 79 ], 80–81% in beef, pork, and mutton [ 75 ], and 128–136% in freshwater fish [ 80 ], similar as in rabbit meat—153% [ 76 ], and lower than that in sea bass ( Dicentrarchus labrax ) fillets—266% [ 81 ]. The level of protein, but also the CS and EAAI in the abdomen and chelae, showed that F. limosus meat is highly digestible and has a well-balanced amino acid composition.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the essential amino acid index (EAAI) calculated for the abdomen and chelae meat of F. limosus was 151.53% and 145.94%, respectively, and it was higher than that for the reference standard protein ( Table 4 ). The EAAI values in this study are higher comparing with the meat of several species, e.g., 114% in lagoon crab Calinectes latimanus [ 77 ], 89% in innards N. maculatus [ 78 ], 50.4–82.9% in chicken [ 75 , 79 ], 80–81% in beef, pork, and mutton [ 75 ], and 128–136% in freshwater fish [ 80 ], similar as in rabbit meat—153% [ 76 ], and lower than that in sea bass ( Dicentrarchus labrax ) fillets—266% [ 81 ]. The level of protein, but also the CS and EAAI in the abdomen and chelae, showed that F. limosus meat is highly digestible and has a well-balanced amino acid composition.…”
Section: Resultsmentioning
confidence: 99%
“…The derivatization of standards and samples was carried out according to Gálvez et al [25]. The identification of amino acids was done through high performance liquid chromatography (Alliance 2695 model, Waters, Milford, MA, USA), using a scanning fluorescence detector (model 2475, Waters) according to Munekata et al [26]. The quantification was done using the external standard technique with amino acid standard (Amino Acid Standard H, Thermo, Rockford, IL, USA).…”
Section: Meat Amino Acid Profilementioning
confidence: 99%
“…This biomass needs to be handled to avoid environmental problems, increasing at the same time resource efficiency to contribute to a sustainable fish supply. Seabass and seabream by-products contain significant amounts of high-quality protein rich in essential amino acids, and fat high in polyunsaturated fatty acids [ 6 , 7 ], making them suitable substrates for valorization. In particular, the application of proteases allows one to disgregate the material into a solid phase rich in mineral, an organic phase rich in fat and an aqueous phase with a high content of soluble protein, peptides and free amino acids [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%